Çağdaş sanatta ekofeminizm ışığında kadın ve doğa - Gündüz, Emine (My University, 2023)
Bu çalışmanın amacı, kadının toprak, ağaç ve doğa ile kurduğu bağları vurgulamak ve bu bağları daha da güçlendirmek amacıyla, çağdaş sanatta ekofeminizm ışığında kadın ve doğayı anlatmaktır. Tezde temel aldığım uygulamalı çalışmalar, pandemi sırasında yaşanan deneyimler ve gözlemler sonucunda, doğanın estetik değerinin hiçe sayılması ve ekolojik dengeye karşı müdahalelerin ortaya çıkması, doğa kaybı ve kadına yönelik şiddet gibi sorunları içermektedir. Kadınların özgürleşmesi, gelecekte gerçekleşeceğine inandığımız umut verici bir gelişme olabilir; ancak bu hedefe ulaşmak için doğanın da özgürleşmesi gerektiğini vurgulamak önemlidir. Bu araştırma ile kadına yönelik şiddet gibi toplumun temel sorunlarına, sanat çalışmalarından örnekler sunarak dikkat çekebilmektir. Bu fikir, toplumsal cinsiyet eşitliğini, ırkçılığa karşı mücadeleyi esas almakta, aynı zamanda insan, hayvan ve diğer tüm canlıların haklarını savunan bir ekolojik yapıya dayanmaktadır. Kadın, doğa ile iç içe geçmiş şekilde tasvir edilmiş ve insan ve doğa arasındaki bağın ne kadar derin ve anlamlı olduğu vurgulanmıştır. Bu araştırma sürecinde ekofeminizmden ilham alarak gerçekleştirdiğim yapıtlar, toplumsal farkındalığın oluşması, sanat, doğa ve toplumsal diyalog üzerine eleştirel düşünmenin sağlanması bakımından önemli olduğuna inanıyorum.

The aim of this study is to tell the story of women and nature in the light of ecofeminism in contemporary art in order to emphasize and strengthen women's bonds with the earth, trees and nature. As a result of the experiences and observations during the pandemic, the applied studies I based my thesis on include problems such as the disregard of the aesthetic value of nature and the emergence of interventions against the ecological balance, loss of nature and violence against women. The emancipation of women may be a promising development that we believe will take place in the future; however, it is important to emphasize that nature must also be liberated in order to achieve this goal. The aim of this study is to highlight the bonds that women have established with the earth, trees and nature, and to tell the story of women and nature in the light of ecofeminism in contemporary art in order to further strengthen these bonds. As a result of the experiences and observations during the pandemic, the applied works I based my thesis on include issues such as the disregard of the aesthetic value of nature and the emergence of interventions against the ecological balance, loss of nature and violence against women. The emancipation of women may be a promising development that we believe will happen in the future, but it is important to emphasize that in order to achieve this goal, nature must also be liberated. The aim of this research is to draw attention to the fundamental problems of society, such as violence against women, by presenting examples from artworks. This idea is based on gender equality, the fight against racism, and an ecological structure that defends the rights of humans, animals and all other living beings. Women are depicted as intertwined with nature, emphasizing how deep and meaningful the bond between humans and nature is. The aim of this research is to draw attention to the fundamental problems of society, such as violence against women, by presenting examples from artworks. This idea is based on gender equality, the fight against racism, and an ecological structure that defends the rights of humans, animals and all other living beings. Women are depicted as intertwined with nature, emphasizing how deep and meaningful the bond between humans and nature is. I believe that the works I have realized in this research process inspired by ecofeminism are important in terms of raising social awareness and providing critical thinking on art, nature and social dialogue.I believe that the works I have realized in this research process inspired by ecofeminism are important in terms of raising social awareness and providing critical thinking on art, nature and social dialogue.
Keywords: Art painting; Arts, Modern; Çağdaş Sanat; Doğa; Doğa Ekofeminizm; Ecofeminism; Ekofeminizm; Kadın; Kadınlar, Sanatta; Resim sanatı; Sanatlar, Modern; Women in art